Artificial defect aggregate as well as preparation method and application thereof
By covering the surface of the concrete base aggregate with acrylic slurry and carbon nanotubes, artificial defective aggregate is formed, which solves the problem of the reduction of compressive strength when concrete improves tensile performance, and improves stability and durability.
Patent Information
- Application Number
- CN202411857235.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art often leads to a significant decrease in compressive strength when improving the tensile performance stability of concrete.
Artificial defective aggregates are made of artificially defective aggregates made of base aggregates such as slag, river sand, quartz sand and other basic aggregates and their surface-covered acrylic slurry and carbon nanotube powder to reduce the cracking strength of concrete by weakening the interface bonding force between the aggregate and the matrix.
While not significantly weakening the compressive strength, the tensile performance stability and ductility of concrete are improved, and the durability of concrete is enhanced.
Smart Images

Figure CN119841569A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based composite materials, and in particular to an artificial defective aggregate and a preparation method and application thereof. Background Art
[0002] Concrete is one of the most commonly used engineering construction materials with excellent compressive strength. However, due to the interface transition zone between the aggregate and the matrix in concrete, the tensile strength of concrete is weak and large cracks are prone to occur, which further accelerates the corrosion of the steel bars inside the concrete and the failure of the overall structure. With the development of infrastructure construction in my country, the durability of concrete materials and their service life in harsh environments have received more and more attention in actual applications. In order to solve this problem, fiber concrete came into being. This new type of concrete uses pure paste or mortar as the matrix and fiber as the reinforcing phase. The prepared concrete can well overcome the shortcomings of traditional concrete, such as low tensile strength, poor ductility, and overall brittleness. Moreover, through the bridging of fibers, the width of cracks can be effectively reduced, further improving the durability of concrete and even giving concrete the ability to self-heal.
[0003] At present, a special concrete material, engineered cement composite (ECC), has received more and more attention. ECC has the characteristics of multi-crack cracking, tensile strain hardening, and ultra-high ductility (about 200 times that of ordinary concrete). In the tensile process, the crack width can be controlled below 100 microns, and it has great self-healing potential. This type of concrete is very suitable for working conditions with complex stress conditions, high durability requirements, and harsh service environments. However, the tensile properties of ECC, that is, multi-crack cracking and ductility, have large variability. This is mainly because in the ECC matrix, the dispersion of fibers and the distribution of original defects in the matrix are different, resulting in large differences in the difficulty of cracking in various parts of the matrix and the bridging ability of fibers. When fractured by external force, the matrix will have different cracking patterns, which seriously affects the stability of ECC performance and hinders the expression of high ductility characteristics of ECC in practical applications. In order to solve this problem, the commonly used method is to add artificial defects in the matrix, so that the distribution of defects in the matrix is more uniform, and the cracking difficulty of each part of the matrix is consistent, which is conducive to the ECC to achieve multi-crack cracking or even saturated multi-crack cracking, and more microcracks mean greater tensile elongation, that is, tensile ductility. However, the artificial defects reported so far, such as rubber particles, expanded shale, plastic balls, etc., all have significant disadvantages, that is, they will greatly weaken the compressive strength of concrete.
[0004] Therefore, it is necessary to find an efficient artificial defect aggregate that can reduce the compressive strength as little as possible while ensuring the high ductility of ECC. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides an artificial defect aggregate and a preparation method and application thereof, which solves the technical problem that when concrete introduces artificial defect aggregate to improve the stability of tensile properties, the compressive strength is significantly reduced.
[0007] (II) Technical solution
[0008] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0009] In the first aspect, an embodiment of the present invention provides an artificial defective aggregate, which is formed by drying a base aggregate and a slurry covering the surface thereof; the base aggregate is at least one of slag, river sand, quartz sand, expanded clay, and waste glass; and the slurry is made by mixing acrylic slurry and carbon nanotube powder.
[0010] Optionally, the mass ratio of the carbon nanotubes to the acrylic acid slurry is (0-3):7, for example, 0:7, 1:7, 2:7 or 3:7.
[0011] Optionally, the mass ratio of the slurry to base aggregate is (1-2):50, for example, 1:50, 1.5:50 or 2:50.
[0012] The mechanism of action of the artificial defect aggregate of the present invention is explained as follows: There are two ways for artificial defect materials to play a defect role. One is that the strength itself is low or loose and porous, which is conducive to the generation of microcracks or cracks running through the entire defect material, such as expanded shale, porous ceramsite, etc.; the other is that the defect material has a weak interface bonding force with the cement matrix, which is also conducive to the generation of microcracks or crack extension, such as rubber particles, plastic balls, etc. In the process of reducing concrete cracking, the number of artificial defects introduced is crucial. Too few defects cannot effectively reduce the difficulty of concrete cracking, and too many defect materials will lead to a significant weakening of the compressive strength. For the above two types of defects, the former is the effective part of the defect as a whole, and it is difficult to reduce its incorporation amount. Although the latter only has the interface in contact with the cement matrix as the effective part, most of the defects themselves do not play a role, so the low efficiency of the defects also limits the reduction of their incorporation amount. In summary, retaining the effective part of the second defect-the weak interface and removing the part that does not play the role of the defect constitutes the core idea of the present invention. The inventor creatively adopted the technical solution of applying artificial defect materials to the surface of the aggregate. Aggregate is one of the raw materials of concrete. It is evenly distributed in the cement matrix and is sufficient in quantity. Simply weakening the interfacial bonding force between aggregate and matrix can effectively weaken the cracking strength of concrete. However, under compression, aggregate can still effectively play the role of force transmission skeleton, so that the overall compressive strength is less weakened. In this way, the amount of defective material added can be greatly reduced without affecting the defect effect.
[0013] In a second aspect, an embodiment of the present invention provides a method for preparing the artificially defective aggregate, comprising the following steps:
[0014] S1, stirring and mixing carbon nanotubes CNT and acrylic acid slurry in a mass ratio of (0-3):7;
[0015] S2, adding the base aggregate to the mixture of S1 and stirring until the surface of the base aggregate is coated with the slurry;
[0016] S3, drying the coated aggregate obtained in S2.
[0017] Optionally, the preparation method further comprises the step of passing the dried coated aggregate in S3 through a 20-200 mesh sieve, and collecting the sieve undersize to obtain the artificial defective aggregate.
[0018] Optionally, the mass ratio of the carbon nanotubes to the acrylic acid slurry is (0-3):7, for example, 0:7, 0.43:7, 1:7, 2:7 or 3:7.
[0019] Optionally, the mass ratio of the carbon nanotubes to the acrylic acid slurry is (1-2):7.
[0020] Optionally, S3 is dried in an oven at a temperature of 75-85°C for 20-25 hours; within 1 hour before drying, the aggregate is turned over every 10-15 minutes, and then drying is continued for 23 hours.
[0021] Optionally, the stirring condition in S1 is stirring at a speed of 1000 to 2000 r / min for 10 to 20 min.
[0022] Optionally, the mass ratio of the mixture to the base aggregate in S2 is (1-2):50, for example, 1:50, 1.5:50 or 2:50.
[0023] Optionally, the step of evenly coating the surface of the aggregate with the sizing agent in S2 is determined based on the color of the aggregate. When the color of the aggregate changes from white to black, the surface of the aggregate is evenly coated with the sizing agent.
[0024] Optionally, the stirring in S2 and the drying in S3 are performed by spraying equipment; wherein the drying temperature is 80 to 150° C. and the drying time is 0.5 to 1 h.
[0025] In a third aspect, an embodiment of the present invention provides an artificially defective aggregate or an application of the artificially defective aggregate prepared by the preparation method in preparing concrete.
[0026] In a fourth aspect, an embodiment of the present invention provides a concrete comprising an artificially defective aggregate.
[0027] In a fifth aspect, an embodiment of the present invention provides a method for preparing concrete, comprising mixing a cementitious material and the artificially defective aggregate described in the first aspect of the present invention, and stirring to obtain a mixture; then mixing a water reducer with water, taking 1 / 2 to 3 / 4 of the volume of the mixture of the water reducer and water and adding it to the mixture, and stirring; then adding fibers to the mixture, and adding the remaining mixture of the water reducer and water; and finally stirring to obtain concrete.
[0028] Optionally, the water reducing agent is a polycarboxylate water reducing agent; the fiber may be polyvinyl alcohol PVA or polyethylene PE.
[0029] (III) Beneficial effects
[0030] The present invention has the following beneficial technical effects:
[0031] (1) The present invention provides an artificial defect aggregate and a preparation method and application thereof. The prepared concrete can reduce the significant decrease in compressive strength by introducing artificial defect aggregate to improve the stability of tensile properties.
[0032] (2) Fewer artificial defect substances are introduced
[0033] The present invention applies artificial defect material (acrylic slurry + CNT) that plays a defect role to the surface of the aggregate to form a thinner defect layer. Compared with directly adding the defect material, the required amount is less.
[0034] (3) The size of artificial defects can be controlled
[0035] The artificial defect in the present invention is prepared by coating aggregate with acrylic slurry, and the size of the entire artificial defect can be directly controlled by the size of the aggregate, so no additional crushing process is required.
[0036] (4) Human defects are more evenly distributed
[0037] The present invention applies defective substances to the surface of aggregates. In the process of preparing concrete, the aggregates can be well distributed through a standard mixing process, thereby indirectly achieving uniform distribution of the defective substances.
[0038] (5) Human-caused defect attributes are controllable
[0039] The present invention can adjust the content ratio of acrylic slurry and CNT to change the properties and surface state of the aggregate defect layer, thereby adjusting the degree of defect of the defective aggregate. CNT is hydrophobic, and its hydrophobic property makes CNT incompatible with cement hydration products, which determines the strength of the interface bonding between aggregate and cement matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is an electronic scan of the artificially defective aggregate of the control group of the present invention;
[0041] Figure 2 This is an electronic scanning image of the man-made defective aggregate in Example 1 of the present invention;
[0042] Figure 3 This is an electronic scanning image of the man-made defective aggregate in Example 2 of the present invention;
[0043] Figure 4 This is an electronic scanning image of the man-made defective aggregate of Example 3 of the present invention. DETAILED DESCRIPTION
[0044] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0045] Example 1
[0046] The method for preparing the artificial defective aggregate of the present invention comprises the following steps:
[0047] S1, placing CNT powder and acrylic acid slurry in a container at a mass ratio of 1:4, and stirring at a speed of 1000 r / min for 10 min;
[0048] S2, take the mixture in S1, add quartz sand, the mass ratio of the mixture to the quartz sand is 1:50, and the particle size of the quartz sand is 70-140 mesh; stir until the surface of the quartz sand aggregate is evenly coated with the slurry;
[0049] S3, take the quartz sand aggregate coated in S2, dry it at 80℃, turn the aggregate every 10 minutes in the first hour, and then continue drying for 23 hours;
[0050] S4, taking the dried coated quartz sand in S3, passing it through a 50-mesh sieve, collecting the sieve residue, and obtaining the artificial defect aggregate;
[0051] The method for preparing concrete using artificially defective aggregate comprises the following steps:
[0052] Mix cement, fly ash, silica fume and artificial defective aggregate and stir for 5 minutes;
[0053] After mixing the water reducer with water, add 3 / 4 of it to the above mixture and stir for 5 minutes;
[0054] Then slowly add PE fiber. During this process, add the remaining 1 / 4 of the mixture of water reducer and water in several times;
[0055] Finally, the concrete slurry was obtained by rapid stirring for 5 min;
[0056] The concrete slurry is molded and cured to obtain concrete.
[0057] The above-mentioned artificial defective aggregates were prepared into concrete, and the proportions were as shown in Table 1:
[0058] Table 1 Concrete mix design (kg / m 3 )
[0059]
[0060] Example 2
[0061] The method for preparing the artificial defective aggregate of the present invention comprises the following steps:
[0062] S1, placing acrylic acid slurry in a container;
[0063] S2, adding quartz sand into S1, the mass ratio of acrylic slurry to quartz sand is 1:50, and the particle size of quartz sand is 70-140 mesh; stirring until the surface of quartz sand aggregate is evenly coated with slurry;
[0064] S3, take the quartz sand aggregate coated in S2, dry it at 80℃, turn the aggregate every 10 minutes in the first hour, and then continue drying for 23 hours;
[0065] S4, taking the dried coated quartz sand in S3, passing it through a 50-mesh sieve, collecting the sieve residue, and obtaining the artificial defect aggregate;
[0066] The method for preparing concrete using artificially defective aggregate is the same as that in Example 1
[0067] Example 3
[0068] The method for preparing the artificial defective aggregate of the present invention comprises the following steps:
[0069] S1, placing CNT powder and acrylic acid slurry in a container at a mass ratio of 3:17, and stirring at a speed of 1000 r / min for 10 min;
[0070] S2, take the mixture in S1, add quartz sand, the mass ratio of the mixture to the quartz sand is 1:50, and the particle size of the quartz sand is 70-140 mesh; stir until the surface of the quartz sand aggregate is evenly coated with the slurry;
[0071] S3, take the aggregate coated in S2 and dry it at 80℃. Turn the aggregate every 10 minutes in the first hour, and then continue drying for 23 hours;
[0072] S4, taking the dried coated quartz sand in S3, passing it through a 50-mesh sieve, collecting the sieve residue, and obtaining the artificial defect aggregate;
[0073] The method for preparing concrete using artificially defective aggregate is the same as that in Example 1
[0074] Example 4
[0075] The method for preparing the artificial defective aggregate of the present invention comprises the following steps:
[0076] S1, placing CNT powder and acrylic acid slurry in a container at a mass ratio of 1:4, and stirring at a speed of 1000 r / min for 10 min;
[0077] S2, take the mixture in S1, add quartz sand, the mass ratio of the mixture to the quartz sand is 1.5:50, and the particle size of the quartz sand is 70-140 mesh; stir until the surface of the quartz sand aggregate is evenly coated with the slurry;
[0078] S3, take the aggregate coated in S2 and dry it at 80℃. Turn the aggregate every 10 minutes in the first hour, and then continue drying for 23 hours;
[0079] S4, taking the dried coated quartz sand in S3, passing it through a 50-mesh sieve, collecting the sieve residue, and obtaining the artificial defect aggregate;
[0080] The method for preparing concrete using artificially defective aggregate is the same as that in Example 1
[0081] Example 5
[0082] The method for preparing the artificial defective aggregate of the present invention comprises the following steps:
[0083] S1, placing CNT powder and acrylic acid slurry in a container at a mass ratio of 1:4, and stirring at a speed of 1000 r / min for 10 min;
[0084] S2, take the mixture in S1, add river sand, the mass ratio of the mixture to the river sand is 1:50, and the particle size of the river sand is 70-140 mesh; stir until the surface of the river sand aggregate is evenly coated with the slurry;
[0085] S3, take the aggregate coated in S2 and dry it at 80℃. Turn the aggregate every 10 minutes in the first hour, and then continue drying for 23 hours;
[0086] S4, taking the dried coated river sand in S3, passing it through a 50-mesh sieve, collecting the sieve residue, and obtaining the artificial defect aggregate;
[0087] The method for preparing concrete using artificially defective aggregate is the same as that in Example 1
[0088] Example 6
[0089] The method for preparing the artificial defective aggregate of the present invention comprises the following steps:
[0090] S1, placing CNT powder and acrylic acid slurry in a container at a mass ratio of 1:4, and stirring at a speed of 1000 r / min for 10 min;
[0091] S2, take the mixture in S1, add slag, the mass ratio of the mixture to the slag is 1:50, and the slag particle size is 70-140 mesh; stir until the surface of the slag aggregate is evenly coated with the slurry;
[0092] S3, take the aggregate coated in S2 and dry it at 80℃. Turn the aggregate every 10 minutes in the first hour, and then continue drying for 23 hours;
[0093] S4, taking the dried coated slag in S3, passing it through a 50-mesh sieve, collecting the sieve underflow, and obtaining the artificial defect aggregate;
[0094] The method for preparing concrete using artificially defective aggregate is the same as that in Example 1
[0095] Example 7
[0096] The method for preparing the artificial defective aggregate of the present invention comprises the following steps:
[0097] S1, placing CNT powder and acrylic acid slurry in a container at a mass ratio of 1:4, and stirring at a speed of 1000 r / min for 10 min;
[0098] S2, take the mixture in S1, add ceramsite, the mass ratio of the mixture to the ceramsite is 1:50, and the particle size of the ceramsite is 70-140 mesh; stir until the surface of the ceramsite aggregate is evenly coated with the slurry;
[0099] S3, take the aggregate coated in S2 and dry it at 80℃. Turn the aggregate every 10 minutes in the first hour, and then continue drying for 23 hours;
[0100] S4, taking the dried coated ceramsite in S3, passing it through a 50-mesh sieve, collecting the sieve underflow, and obtaining the artificial defect aggregate;
[0101] The method for preparing concrete using artificially defective aggregate is the same as that in Example 1
[0102] Comparative Example 1
[0103] Aggregate not coated with slurry
[0104] Mix cement, fly ash, silica fume and aggregate and stir for 5 minutes;
[0105] After mixing the water reducer with water, add 3 / 4 of it to the above mixture and stir for 5 minutes;
[0106] Then slowly add PE fiber. During this process, add the remaining 1 / 4 of the mixture of water reducer and water in several times;
[0107] Finally, the concrete slurry was obtained by rapid stirring for 5 min;
[0108] The concrete slurry is molded and cured to obtain concrete.
[0109] Concrete was prepared from the artificially defective aggregates of Examples 1-3 and the untreated aggregate of the control example, and steam-cured at 75° C. for 3 days. After being placed for 7 days, compressive strength and tensile tests were performed. The experimental results are shown in Table 2.
[0110] Table 2 Mechanical properties of concrete prepared in Examples 1-3 and the blank control group
[0111]
[0112] Comparative Example 2
[0113] Coarse river sand is used as the artificial defect aggregate, and the rest is the same as that of Control Example 1.
[0114] Comparative Example 3
[0115] The artificial defect aggregate is air glass microspheres, and the rest is the same as control example 1.
[0116] Comparative Example 4
[0117] PE balls are used as the artificial defect aggregate, and the rest are the same as in Control Example 1.
[0118] Comparative Example 5
[0119] The artificial defective aggregate is super absorbent polymer (SAP), and the rest is the same as that of Control Example 1.
[0120] Comparative Example 6
[0121] The artificial defect aggregate is rubber particles, and the rest is the same as that of Control Example 1.
[0122] Comparative Example 7
[0123] The artificial defect aggregate adopts oligomer aggregate (GPA), and the rest is the same as control example 1.
[0124] Table 3 Δδ / Δσ values of concrete prepared with artificial defects in comparative examples 2-7
[0125]
[0126] Here, the ratio of the ultimate strain growth rate to the compressive strength growth rate is used to measure the efficiency of artificial defects, that is, Δδ / Δσ. It should be noted that the negative sign represents that the artificial defect will reduce the compressive strength of concrete. The larger the absolute value of this value, the more ultimate strain is brought about by the loss of unit compressive strength, which means that the efficiency of the artificial defect is higher; the positive sign represents that the artificial defect will increase the compressive strength of concrete.
[0127] Table 2 summarizes the efficiency values of the artificial defect aggregates prepared in Examples 1-3. As can be seen from Table 2, the artificial defect aggregate represented by Example 3 has the best effect, which can improve the ultimate strain of concrete and the compressive strength of concrete; the efficiency of the artificial defect aggregate prepared in Example 2 is higher than that in Example 1. The overall efficiency of the artificial defect aggregates in Examples 1-3 of the present invention is better than the efficiency values of the artificial defects in Comparative Examples 2-7.
[0128] In order to demonstrate the differences in the artificially defective aggregates prepared in Examples 1-3, the three coated aggregates were microscopically characterized. Figure 1-Figure 4 Shown are scanning electron micrographs of the coated aggregates of the control example and Examples 1-3 of the present invention. Figure 1-4The states of the aggregate surface at three CNT / polymer ratios are shown. As the CNT content increases, the amount of CNT exposed on the aggregate surface increases, the interface bonding with the matrix becomes worse, and the defect properties become stronger. It can be seen from the figure that different CNT contents lead to large differences in the morphology of the aggregate surface. In Example 1, the CNT content is the highest. It can be seen that the aggregate surface is almost covered by CNT, and CNT is hydrophobic, which makes the aggregate surface also have a certain hydrophobicity, thereby reducing the compatibility of the aggregate with the cement matrix and playing the role of a defective layer; in Example 2, no CNT is added, so that the aggregate surface is all acrylic slurry, and although the acrylic slurry is hydrophilic and can promote the hydration of cement on its surface, its elastic modulus is low, which also indirectly plays the role of a defective layer; in Example 3, the aggregate surface has both CNT and acrylic slurry, which makes the aggregate surface form a local hydrophilic and local hydrophobic structure, and the presence of CNT also makes up for the disadvantage of the small elastic modulus of the acrylic slurry, which makes the artificial defective aggregate in Example 3 play an enhancing role to a certain extent, but due to the presence of the coating, the bonding force between the aggregate and the matrix is still less than the bonding force between the aggregate and the matrix in the blank group, which makes the aggregate in Example 3 still have defective properties that weaken the interfacial bonding force, thereby playing a role in increasing ductility.
[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An artificially defective aggregate, characterized in that: The slurry is formed by drying a basic aggregate and a slurry covering the surface thereof; the basic aggregate is at least one of slag, river sand, quartz sand, ceramsite and waste glass; and the slurry is made by mixing acrylic slurry and carbon nanotube powder.
2. The artificial defective aggregate according to claim 1, characterized in that: The mass ratio of the carbon nanotubes CNT to the acrylic acid slurry is (1-2):
7.
3. The artificial defective aggregate according to claim 1, characterized in that: The mass ratio of the slurry to the base aggregate is (1-2):
50.
4. A method for preparing an artificially defective aggregate according to any one of claims 1 to 3, characterized in that: The steps include: S1, stirring and mixing carbon nanotubes CNT and acrylic acid slurry powder in a mass ratio of (0-3):7; S2, adding the base aggregate to the mixture of S1 and stirring until the surface of the base aggregate is coated with the slurry; S3, drying the coated aggregate obtained in S2.
5. The method for preparing artificial defective aggregate according to claim 4, characterized in that: The preparation method further comprises the steps of passing the dried coated aggregate in S3 through a 20-200 mesh sieve, and collecting the sieve underflow to obtain the artificial defective aggregate.
6. The method for preparing artificial defective aggregate according to claim 4, characterized in that: The mass ratio of the carbon nanotubes to the acrylic acid slurry is (1-2):
7.
7. The method for preparing artificial defective aggregate according to claim 4, characterized in that: The mass ratio of the mixture to the base aggregate in S2 is (1-2):
50.
8. The method for preparing artificial defective aggregate according to claim 4, characterized in that: The temperature of the drying treatment in S3 is 75-85°C and the time is 20-25h.
9. Use of the artificial defect aggregate according to any one of claims 1 to 3 or the artificial defect aggregate prepared by the preparation method according to any one of claims 4 to 8 in preparing concrete.
10. A concrete, characterized in that: It comprises the artificial defect aggregate according to any one of claims 1 to 3.
11. A method for preparing concrete, characterized in that: The cementitious material and the artificial defect aggregate according to any one of claims 1 to 3 are mixed and stirred to obtain a mixture; then a water reducer is mixed with water, and 1 / 2 to 3 / 4 of the volume of the mixture of the water reducer and water is added to the mixture and stirred; then fibers are added to the mixture, and the remaining mixture of the water reducer and water is added; and finally, concrete is obtained by stirring.